2002
DOI: 10.1016/s1097-2765(02)00690-1
|View full text |Cite
|
Sign up to set email alerts
|

Design, Activity, and Structure of a Highly Specific Artificial Endonuclease

Abstract: We have generated an artificial highly specific endonuclease by fusing domains of homing endonucleases I-DmoI and I-CreI and creating a new 1400 A(2) protein interface between these domains. Protein engineering was accomplished by combining computational redesign and an in vivo protein-folding screen. The resulting enzyme, E-DreI (Engineered I-DmoI/I-CreI), binds a long chimeric DNA target site with nanomolar affinity, cleaving it precisely at a rate equivalent to its natural parents. The structure of an E-Dre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
161
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(166 citation statements)
references
References 44 publications
3
161
0
2
Order By: Relevance
“…The DNA cleavage domain of the type IIS REase FokI was fused with DNA binding proteins such as the Drosophila Ubx homeodomain (27), the yeast Gal4 protein (28) and zinc-finger proteins (29) to engineer chimeric endonucleases. Furthermore, it was demonstrated that domains from unrelated homing endonucleases or mutated subdomains of an individual homing enzyme can be fused to create active chimeric enzymes of altered specificity (30)(31)(32)(33). However, the hybrids mentioned above are extremely rarely cutting enzymes, which have specific applications including gene therapy (34,35), but their potential to be used as analytical tools like conventional type II REases is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA cleavage domain of the type IIS REase FokI was fused with DNA binding proteins such as the Drosophila Ubx homeodomain (27), the yeast Gal4 protein (28) and zinc-finger proteins (29) to engineer chimeric endonucleases. Furthermore, it was demonstrated that domains from unrelated homing endonucleases or mutated subdomains of an individual homing enzyme can be fused to create active chimeric enzymes of altered specificity (30)(31)(32)(33). However, the hybrids mentioned above are extremely rarely cutting enzymes, which have specific applications including gene therapy (34,35), but their potential to be used as analytical tools like conventional type II REases is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Thus a sequence-specific nuclease or targeted DNA damage would be the basis of a strategy for manipulation of the genome. Although considerable effort has been given to the development of chimeric nucleases for this purpose (17,18), the alternate approach based on targeted DNA damage has received much less attention (9,19).…”
mentioning
confidence: 99%
“…S4). In contrast, 3 Mg 2ϩ were reported for I-CreI (17) and H-DreI active sites (15), even though in the last case the DNA remained intact. Two of the metal ions were unshared, whereas the central one was shared between the 2 catalytic residues (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The structure of the I-DmoI/DNA complex also depicts differences when compared with H-DreI (Fig. S2) (15), a chimerical enzyme that contains the domain A of I-DmoI fused to an I-CreI monomer (originally named E-DreI). A comparison between the wild type structure and the I-DmoI domain A of the chimera reveals subtle changes in the DNA conformation (see below).…”
Section: Resultsmentioning
confidence: 99%